ECONOMIC POLICY ALIGNMENT AND ITS IMPACT ON ECONOMIC PERFORMANCE: A CASE STUDY OF THE KINGDOM OF SAUDI ARABIA (2003-2023) - Doctor Hayder Oleiwi Shami (Scholar Express Journals, 2025)
One of the most significant tools of the overall economic policy of a state is monetary and fiscal policies. A state tends to establish rudimentary economic targets which reflect the aspirations of its overall economic policy and aims to fulfill them with the weapons and mechanisms of these two policies. Considering the great importance of each of the policies individually, coordination and alignment between the goals and mechanisms of each policy are necessary rather than just needed to prevent disagreement and contradiction between the desired policy goals and the mechanisms of the policy as well as doing the same to the means and ends of each policy as a whole.
Keywords: Economic policy; monetary policy alignment; fiscal policy alignment